Assessment of value chain system for horticulture in Khyber Pakhtunkhwa including Newly Merged Districts (former FATA) - Rana, Abdul Wajid; ul Haq, Zahoor; Asghar, Sobia; Haider, Zeeshan; Davies, Stephen (International Food Policy Research Institute, 2021)
Rapid urbanization and rising income levels in developing countries, such as Pakistan, changing diet habits, information and communication technologies, structural transformation in retail markets as well as export market opportunities are catalyzing dynamic change in horticulture value chains. This is causing a paradigm shift in the way horticulture products are produced, processed, and sold, both within domestic markets and in export markets across the globe. The emergence of local, regional, and global value chains is contributing to increasing engagement of the private sector in horticulture, as these firms and markets look for better quality, greater productivity, efficiency, and market penetration. At the same time, consumers demand for safety, quality, convenience and affordable prices is underlining the role of the private sector in the efficacy of the value chains.